Comparison of Comprehensive Screening Results in Postmortem Blood and Brain Tissue by UHPLC–QTOF-MS. Issue 9 (14th February 2022) - Hansen, Stine Lund; Dalsgaard, Petur Weihe; Linnet, Kristian; Rasmussen, Brian Schou
Abstract: Alternative specimens collected during autopsies can be valuable in postmortem toxicology in cases where peripheral blood is not available. The applicability of brain tissue as an alternative matrix for drug screening by ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry was investigated in this study. Results of the 50 most frequently detected drugs and metabolites of toxicological interest in blood and brain tissue samples from 1, 719 autopsy cases were compared. Examination of the results in paired blood and brain tissue samples revealed that the two matrices were in general comparable, as the majority of the 50 analytes were observed in a high number of the examined cases in both blood and brain tissue. This demonstrates the potential of brain tissue as an alternative matrix for drug screening in postmortem toxicology or as a secondary matrix for confirmation.